Elite Cues, News Coverage, and Partisan Support for Compromise. (September 2017) - McLaughlin, Bryan; McLeod, Douglas M.; Davis, Catasha; Perryman, Mallory; Mun, Kwansik
In accordance with self-categorization theory, this study predicts that because elite cues affect partisans' perceptions of group norms, news coverage of political gridlock should influence partisans' willingness to endorse compromise. Results of two experimental studies, where Republican and Democratic samples read a news story in which group leaders were either willing or unwilling to compromise, largely support our expectations. However, we also find evidence that willingness to compromise can depend on the specific issue context, as well as pre-existing attitudes. These results further our understanding of how media coverage affects the functioning of democracy in the United States.